The Influence of Original Revenue and Transfer Revenue on Capital Expenditure in South Tangerang City - Mu'am, Ahmad; Nurdin, Nurliah; Sudrajat, Agus; Karunia, R. Luki (Universitas Muhammadiyah Mataram, 2023)
The purpose of this study is to determine and analyze the effect of own-source revenue and transfer revenue on capital expenditure in South Tangerang City. The data used is time series data regarding local own-source revenue and transfer revenue on capital expenditure in South Tangerang City 2012-2021. Data analysis methods include Multiple Regression Analysis, t test, and coefficient of determination analysis. From the Multiple Regression Analysis, the regression equation Y=1.03819 + 0.521X2-0.612X3 is obtained. The constant of 1.03819 means that the increase in capital expenditure allocation is 1.03819 percent if there is no increase in local revenue and transfer revenue. The regression coefficient of the local own-source revenue variable shows a positive influence on capital expenditure of 0.521. From the t-test results, it can be explained that local own-source revenue has a significant effect on capital expenditure, where the t-count> t-table value is obtained (2.701> 2.306). The regression coefficient of the local own-source revenue variable shows a negative effect on capital expenditure of 0.612. From the t-test results, it can be explained that transfer revenues have a significant effect on capital expenditures in South Tangerang City, where the t-count value is obtained < t-table (1.259 < 2.306). From the coefficient of determination analysis, it is known that local revenue and transfer revenue affect capital expenditure by 47.4%, while the remaining 52.6% is influenced by other variables outside this research model. Increased capital expenditure has an important role because it has a long-term benefit period to provide services to the public because infrastructure development and the provision of various facilities are carried out to increase investment attractiveness. Industrial infrastructure development has a real impact on the increase in local revenue. So that if the Regional Government wants to improve public services and people's welfare by increasing capital expenditure, then the Regional Government must strive to explore as much local revenue as possible.